The Reflection of War in Contemporary Ceramic Art in The Kurdistan Region/Iraq - Hunar Muhammad Tofiq (QALAAI ZANIST JOURNAL, 2024)
This paper examines the reflection of war in contemporary ceramic art in the Kurdistan Region/Iraq The first part of the research is about the research problem, the importance of the research, the limitations and time of the research, the purpose, importance and definition of terms. The second part of the study, which is part of the theoretical framework of the research, focuses on the history of war in the art of painting, especially those artistic works that reflected the theme of war and had a reflection among artists around the world. The second part of the second research is concerned with Kurdish artists who through their artistic works reflect the tragedy and misery that has befallen the Kurdish nation, narrate and criticize it. Research Implementation: 1. Research community, 2. Research sample, 3. Research tools, 4. Data collection tools, 5. Research methods. Chapter 4 About Results. The subject of war in contemporary ceramic art in the Kurdistan Region/Iraq includes the task of documenting and archiving the history of the subjects, some of which directly transfer the prominent figures of events into their work or deal with the subject at the level of symbols. The embodiment of war memories is done in ceramic techniques and styles, which depends on the style and technique of the artist who records the memories. 3. The reference to the subject of war in examples (1-2) appears at the level of title and content of the work